MOTOR SALES SYSTEM IN PT. ARTHA WAHANA HARSAKA APPLICATIONS USING MICROSOFT VISUAL BASIC.NET - Fitria Kurniati; Cut Asiana Gemawaty, SKom, MMSi (Jurnal Sistem Informasi, 2006)
PT. Wahana Artha Mulya Harsaka Coral branch is engaged in the sale of motorcyclesfrom Honda Motor Astra Honda manifold. Products marketed by various kindsranging from the Honda Legend, Supra, Supra X / XX until new products are issuedby Astra Honda Motor, Honda Karisma Namely with disc brakes and the wearTromol.Scientific writing is about a system designed to solve problems related to vehiclesales in cash and the issuance of reports and calculations are done manually if thereare mistakes that can be detrimental to all concerned.System design was done by using a data flow diagram (DFD) as a tool accessories.The design of the database is done by using the concept of an Entity RelationshipDiagram (ERD) and the concept of normalization. Programming language usingMicrosoft Visual Basic.NET.